PENDIDIKAN KEBERUNTUNGAN (Pemahaman Qs. Al-Mu’minun : 1-9 dalam Perspektif Tafsir Tarbawy) - Afandi, Irfan (INCARE, International Journal of Educational Resources, 2022)
This study tries to understand how to be a lucky person in life in the perspective of tarbawy interpretation. Thus, luck can be something that man can achieve in his mortal life. The approach used in this article is a contextual approach, namely the context of the interpreter in which the context exists and surrounds the current reader. The results of the study stated that actually lucky people are people who are in a situation of low self-control. This has to do with the power of Allah Almighty, who is almighty of all things. Allah Almighty mentioned in Qs. al-Mu'minun that the mu'min person was lucky because he did 6 (six) things, namely khusyu prayer', leaving useless things, fulfilling zakat, Keeping the pubic, Keeping the mandate / Promise, Keeping the prayer time. So, the purpose of Luck education in this article is education by referring to students understanding, loving and doing these 6 (six) things in order to become lucky people.